2021
DOI: 10.1002/mp.14927
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning‐based coronary artery motion estimation and compensation for short‐scan cardiac CT

Abstract: During a typical cardiac short scan, the heart can move several millimeters. As a result, the corresponding CT reconstructions may be corrupted by motion artifacts. Especially the assessment of small structures, such as the coronary arteries, is potentially impaired by the presence of these artifacts. In order to estimate and compensate for coronary artery motion, this manuscript proposes the deep partial angle-based motion compensation (Deep PAMoCo). Methods: The basic principle of the Deep PAMoCo relies on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…We achieved a similar AUC of 0.88 with a single coronal MPR image per CTPA examination. Other studies [17,19] [20] Based on the identification and estimation of motion artifact, other investigators have reported on motion artifact correction and compensation solutions for head and cardiac CT examinations [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We achieved a similar AUC of 0.88 with a single coronal MPR image per CTPA examination. Other studies [17,19] [20] Based on the identification and estimation of motion artifact, other investigators have reported on motion artifact correction and compensation solutions for head and cardiac CT examinations [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al . reported a fully automatic AI for grading image quality (motion artifacts) of CCTA using semi-automatic labeling and tracking of the coronary arteries [20] Based on the identification and estimation of motion artifact, other investigators have reported on motion artifact correction and compensation solutions for head and cardiac CT examinations [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Some approaches use (image and/or feature) registration between a series of half -scan reconstructions. 11,20 Recently, deep learning networks have also been used effectively to estimate and correct for motion in CT. 16,21,22 Finally, the concept of using PARs has been used to facilitate robust motion estimation, with correspondences being found in conjugate pairs of PAR images. 15,23 It is interesting to note that backproject-then-warp motion compensation as well as PAR-based motion estimation both rely on essentially breaking up the sinogram data into smaller sections in time and representing these in the image domain as PAR images.…”
Section: Recent Progress In Motion-compensated Reconstructionmentioning
confidence: 99%
“…Some approaches use (image and/or feature) registration between a series of half‐scan reconstructions 11,20 . Recently, deep learning networks have also been used effectively to estimate and correct for motion in CT 16,21,22 . Finally, the concept of using PARs has been used to facilitate robust motion estimation, with correspondences being found in conjugate pairs of PAR images 15,23 …”
Section: Introductionmentioning
confidence: 99%
“…Motion compensation for interventional CBCT has gained significant attention, with image-based approaches including autofocus methods based on handcrafted metrics [1][2][3], and methods leveraging deep convolutional neural networks (CNNs) to directly learn motion trajectories from distortion patterns [4], or to learn features associated to motion effects that are aggregated into deep autofocus metrics [5,6]. Common to those approaches is the need for simulation methods that allow the generation of large amounts of realistic, motion-corrupted, CBCT data to enable training and evaluation.…”
Section: Introductionmentioning
confidence: 99%